2023
DOI: 10.2147/ccid.s408958
|View full text |Cite
|
Sign up to set email alerts
|

Skin Manifestations Among Patients Admitted with COVID-19: A Cross-Sectional Study at a University-Based Tertiary Hospital in Jordan

Diala M Alshiyab,
Firas A Al-qarqaz,
Enas Alhaje
et al.

Abstract: Background COVID-19 pandemic hit the entire world with severe health and economic consequences. Although the infection primarily affected the respiratory system, it was soon recognized that COVID-19 has a multi-systemic component with various manifestations including cutaneous involvement. Objective The main objective of this study is to assess the incidence and patterns of cutaneous manifestations among moderate-to-severe COVID-19 patients who required hospitalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…One predisposing risk factor is low vitamin D levels, which was shown to be predictive factor of a psoriatic flare post COVID-19 vaccination [18]. Furthermore, a recent study by Alshiyab et al, 2023, found a significant association between smoking and the development of skin eruptions during an acute COVID-19 infection [19]. Pertinent to our patient, as described above, second-hand smoke exposure is also associated with COVID-19-related skin eruptions, but this usually occurs in the context of a severe COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…One predisposing risk factor is low vitamin D levels, which was shown to be predictive factor of a psoriatic flare post COVID-19 vaccination [18]. Furthermore, a recent study by Alshiyab et al, 2023, found a significant association between smoking and the development of skin eruptions during an acute COVID-19 infection [19]. Pertinent to our patient, as described above, second-hand smoke exposure is also associated with COVID-19-related skin eruptions, but this usually occurs in the context of a severe COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of the novel Coronavirus disease-19 (COVID-19) infection has seen cases of EM being reported as a cutaneous complication, either to the infection itself or to the vaccine ( 14 , 15 ). EM due to COVID-19 vaccination occurred most often after the first dose, most commonly with mRNA vaccines in one study ( 15 ).…”
Section: Erythema Multiformementioning
confidence: 99%